2017
DOI: 10.1007/s10508-017-0937-1
|View full text |Cite
|
Sign up to set email alerts
|

The Exploitive Mating Strategy of the Dark Triad Traits: Tests of Rape-Enabling Attitudes

Abstract: The Dark Triad traits have been repeatedly labeled as facilitating an exploitive mating strategy. However, various researchers have repeatedly conflated short-term mating or casual sex with an exploitive mating strategy. In this study using Mechanical Turk participants (N = 252; 142 men, 110 women), we provided a better test of just how sexually exploitive those high on the Dark Triad traits might be by examining how the traits related to rape-enabling attitudes. We examined how each trait may facilitate rape,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
62
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 65 publications
5
62
0
2
Order By: Relevance
“…For example, this is demonstrated in sexual aggression, such that each trait is linked to sexual coercion (Figueredo, Gladden, Sisco, Patch, & Jones, 2015) and rape-enabling attitudes (Jonason, Girgis, & Milne-Home, 2017), although it appears narcissism might play a particularly weak role when sufficiently isolated (Jonason, 2015a). For example, this is demonstrated in sexual aggression, such that each trait is linked to sexual coercion (Figueredo, Gladden, Sisco, Patch, & Jones, 2015) and rape-enabling attitudes (Jonason, Girgis, & Milne-Home, 2017), although it appears narcissism might play a particularly weak role when sufficiently isolated (Jonason, 2015a).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…For example, this is demonstrated in sexual aggression, such that each trait is linked to sexual coercion (Figueredo, Gladden, Sisco, Patch, & Jones, 2015) and rape-enabling attitudes (Jonason, Girgis, & Milne-Home, 2017), although it appears narcissism might play a particularly weak role when sufficiently isolated (Jonason, 2015a). For example, this is demonstrated in sexual aggression, such that each trait is linked to sexual coercion (Figueredo, Gladden, Sisco, Patch, & Jones, 2015) and rape-enabling attitudes (Jonason, Girgis, & Milne-Home, 2017), although it appears narcissism might play a particularly weak role when sufficiently isolated (Jonason, 2015a).…”
mentioning
confidence: 99%
“…It has been suggested that the Dark Triad traits reflect a meaningful and evolutionary relevant latent construct (Jonason et al, 2009), and idea that has received support from overseas researchers (Bertl, Pietschnig, Tran, Stieger, & Voracek, 2017) and those parsing the shared and unique variance using structural equation modelling in relation to important outcomes like sexual assault (Figueredo et al, 2015;Jonason, Girgis, & Milne-Home, 2017). This has both conceptual and measurement implications.…”
mentioning
confidence: 99%
See 3 more Smart Citations